Increasing Knowledge of Mothers of Toddlers About Balanced Nutrition Education as an Effort to Prevent Stunting by Using Booklet Media - Yolanda Anastasia Sihombing; Jenti Sitorus; Elfrida Nainggolan (CV. AFDIFAL MAJU BERKAH, 2023)
The aim of writing this case study is to increase the knowledge of mothers with stunting toddlers about balanced nutrition by providing education using booklets. The method used is descriptive research using a case study approach. Case studies were conducted on respondents who met the research criteria. The intervention was carried out for 5 days. Results: After 5 days of intervention, namely efforts to increase knowledge among mothers with stunted toddlers regarding balanced nutrition education using booklet media. The results obtained were that the mother's level of knowledge increased where on the fifth and third day the client was able to do what the researcher taught. The conclusion can be drawn that providing nutrition education using booklet media is able to increase knowledge in mothers with stunted toddlers.